ЎҚУВЧИЛАР ИНТЕЛЛЕКТУАЛ РИВОЖЛАНИШИДА ПСИХОЛОГИК ТРЕНИНГ МАШҒУЛОТЛАРИНИНГ АҲАМИЯТИ - Бекназарова, Л.С. (SCIENCE and SOCIETY, 2020)
This article deals with the organization and conduct of psychological training sessions focuses on the intellectual development of students, as well as the formation of functions such as intellectual activity, decision making, time manadement, goal setting, responsibility.
Keywords: education system; teacher; student; intellect; psychological feature; pedagogical technology; training; knowledge; skill